Investment analytics (FIN382) / Ahamd Firdaus Mohd Tarmizi ... [et al.] - Mohd Tarmizi, Ahamd Firdaus; Tumin, Muhammad Shahrul Nizam; Ismail, Muhammad Zaid Aidil; Mohd Roosdi, Mohamad Irfan Danish; Mohamad Arif, Mohamad Zarif Syamil (2019)
Economy analysis involves assessing or examining topics or issues from an economist’s perspective. Economic analysis is the study of economic system of a country. It may also be a study of production or processes of a country. The analysis is to determine the effectiveness or efficiency the country’s performance. In this analysis, there are world countries, regional and third world countries. World or first world country is the country that is aligned within NATO and opposed to the Soviet Union (United Kingdom, United States, France, Italy and Japan). Meanwhile, regional country is the Asean’s country (Singapore, Vietnam, Philippines, Brunei and Indonesia) and third world country is the country that is not aligned with NATO and a lack in the development of the country, (Jamaica, Peru, and Niger).